Clot Formation Within Tracheostomy Tube in Surgical Unit 1 of HFH Hospital Rawalpindi; a Quality Improvement Project - Abdul Hafeez Soomroo, Shanza Nazih, Ahsan Hameed, Rai Asghar, Aayet Zulfiqar (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Clotting inside tracheostomy tubes is a major problem that can block the airway and trigger breathing problems, more especially among critical care patients. This clinical audit is a full report of the Tracheostomy Care Practice in the Surgical Intensive Care Unit (ICU) of Holy Family Hospital (HFH) Rawalpindi, where we evaluated the current situation, identified risk factors for clot formation, and made recommendations for improvement. It was a combined retrospective and prospective review, and it was from January to February 2025, the period when 50 patients who underwent tracheostomy and remained in the ICU for more than 48 hours were involved. The data were primarily based on patient’s medical records, clinical documentation, and incident reports. The study found out that the incidence rate of clot formation was 20% because of the lack of enough humidification (50%), infrequent suctioning (30%), and airway trauma (20%) as the most significant risk factors. The support of recommended measures was still ineffective with 60% of the oxygen that was only humidified and suctioning being done at appropriate intervals was in 70% of cases. The outcomes contained in the research impress the significance of standard tracheostomy care protocols, better-equipped staff, and frequent audits so that the patients’ safety is improved and the obstructions of the airways risk is minimized. The implementation of these measures is the key to obtaining better results for the ICU patients undergoing tracheostomy surgery.